TV SONG SHOW: COMPETITION OF GHOSTS OR THE GHOST OF GOMPETITION? / ПЕСЕННОЕ ТЕЛЕШОУ: КОНКУРЕНЦИЯ ПРИЗРАКОВ ИЛИ ПРИЗРАК КОНКУРЕНЦИИ? - Druzhkin Y.S. / ДРУЖКИН Ю.С. (Наука телевидения)
The article discusses TV game shows («Field of Dreams», «Behind the Glass», etc.), which in one form or another reproduce the elements of the capitalist myth. They «rehabilitate» the image of money in particular, «big money» and the desire to earn (win, gain) a large amount. In TV programs the implementation of ongoing schemes (equal opportunities – gameplay – final inequality) reflected the myth of capitalism and its television incarnation that conveys the spirit of our time.